Keratinising squamous metaplasia of the bladder. (16th August 2018) - Bell, Chris; Meara, Natalie; Gulur, Dev; Middela, Seshikanth
Abstract : Keratinising squamous metaplasia of the bladder is a very rare entity that carries a risk of progression to malignancy. We present a case of a 62-year-old man found to have the condition and discuss the management dilemma with a review of the literature.